Information and Communication Technologies for the Promotion of Open and Distance Learning in Bangladesh - Islam, Md Tofazzal; Selim, Abu Sadeque Md. (Journal of Agriculture & Rural Development, 2008)
Recent explosion of information and communication technologies (ICTs) in the developed countries offers tremendous opportunities for electronic delivery of course materials for open and distance learners. In spite of some socio-economic constraints, ICTs are expanding fastly in the developing countries and thus offer a new scope for the promotion of open and distance learning. Bangladesh is recently connected to the information super-highway through submarine cables, which will add a new spin in the expansion of the Internet and other ICTs. More than 10 million mobile phone users throughout the country reflect the real phenomenon of quick acceptance of the modern ICTs by the people. However, the only distance teaching public university, Bangladesh Open University (BOU) is still far behind of using modern ICTs for delivering her course materials to the distance learners. Considering the rapid expansion of computer and internet after 1998s, it is now appropriate time to consider inclusion of some interactive ICTs i.e. e-learning in delivering course materials of BOU and other academic institutes to promote distance education in Bangladesh. In this paper, we discuss the current situation and future prospects of ICTs in Bangladesh for the expansion of open and distance education. Key words: ICTs, ODL, mobile learning.